2015
DOI: 10.1186/s12876-015-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of vasopressin V2-receptor antagonists in cirrhosis patients with ascites: a meta-analysis of randomized controlled trials

Abstract: BackgroundAscites is the most common complication of cirrhosis. It may lead to the consequence of poor prognosis and the deterioration of quality of life. Asopressin V2 receptor antagonists is a kind of vaptans, and it has been proved to be effective in hyponatremia patients. We conducted a meta-analysis about treatment of vaptans in cirrhosis patients with ascites.MethodsFollowing our selection criteria, we collected a total of 14 studies containing 16 randomized controlled trials (2620 patients) from a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
0
38
0
3
Order By: Relevance
“…In contrast, a previous meta-analysis found that tolvaptan treatment did not have survival benefits [10]. A retrospective study showed that longer survival was found in patients responding to tolvaptan therapy [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a previous meta-analysis found that tolvaptan treatment did not have survival benefits [10]. A retrospective study showed that longer survival was found in patients responding to tolvaptan therapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The vasopressin V2 receptor antagonist, tolvaptan, which was developed in Japan, was shown effective in 50–60% of cirrhotic patients with ascites refractory to conventional diuretics [7-9]. A meta-analysis also found that vasopressin V2 receptor antagonists improved hyponatremia and may improve symptoms in cirrhosis patients with refractory ascites [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Pada sirosis hati dengan ascites permagna, pengukuran lingkar perut merupakan variabel yang harus dilakukan untuk memonitor efek diuretik. 16,17 Pengukuran lingkar perut bersifat subject to error karena bergantung pada posisi pasien dan lokasi pengukuran pada abdomen.…”
Section: Evaluasi Efektivitas Penggunaan Kombinasi Spironolakton Dan unclassified
“…Günümüzde, sadece tolvaptan ve conivaptan onay almıştır. Maliyetleri yüksektir, bu nedenle düşük ücretli diüretik gibi ilaçlarla karşılaştırıldığında klinik kullanımları sınırlıdır (32).…”
Section: İlaçlar öNerilerunclassified
“…Güvenilir, iyi tolere edilebilir ve oral kullanımı sayesinde güvenli bir şekilde ayaktan hastaya başlanabilir, ancak daha çok çalışmaya ihtiyaç vardır. Sonuç olarak, şimdiki veriler ışığında siroz tedavisinde vaptanların rutin kullanımını önerilmiyor (32).…”
Section: İlaçlar öNerilerunclassified